Pengaruh Kemampuan dan Motivasi Guru terhadap Prestasi Belajar Siswa Kelas XI SMKN-2 Palangka Raya - Sumarnie (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2020)
The research aims to described the significance of the effect of : 1) theteacher's ability on the student achievement, 2) the teachers’ motivation toteach on student achievement, 3) the teachers’ ability and motivation toteach on student achievement in class XI Sekolah Menengah KejuruanNegeri (SMKN-2) Palangkaraya. The method used the survey methodassociative exsploration level with the relationship of causal variables andtypes of quantitative data. The population as sampel of research of 35students by taking all members of the